2018
DOI: 10.5530/ajbls.2018.7.4
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Antibiotic Sensitivity of Escherichia coli and Salmonella spp. in Retail Chicken Meat at Selected Markets in Valencia City, Bukidnon, Philippines

Abstract: Aim: Contaminated retail chicken meat has been implicated with food poisoning caused by Escherichia coli and Salmonella spp. The present study was aimed to determine the occurrence and antibiotic sensitivity of E. coli and Salmonella spp. in retail chicken meat at selected markets in Valencia City, Bukidnon, Philippines. Methods: A total of 50 retailed chicken meats which comprised of drumsticks (n=25) and wings (n=25) were collected aseptically from three selected markets (2 supermarkets and 1 wet market) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…In the present study, 54.6% of the samples were contaminated with E. coli , with the highest prevalence being observed in chicken meat (70.6–82.7%). The high-level contamination of E. coli in chicken was consistent with that reported by previous studies conducted in the Philippines [ 15 , 22 ], China [ 23 ], and Bangladesh [ 24 ]. Contamination of meat samples with pathogenic E. coli usually indicates poor hygiene during slaughter and handling, and unsuitable storage after slaughter [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, 54.6% of the samples were contaminated with E. coli , with the highest prevalence being observed in chicken meat (70.6–82.7%). The high-level contamination of E. coli in chicken was consistent with that reported by previous studies conducted in the Philippines [ 15 , 22 ], China [ 23 ], and Bangladesh [ 24 ]. Contamination of meat samples with pathogenic E. coli usually indicates poor hygiene during slaughter and handling, and unsuitable storage after slaughter [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…The high-level contamination of E. coli in chicken was consistent with that reported by previous studies conducted in the Philippines [ 15 , 22 ], China [ 23 ], and Bangladesh [ 24 ]. Contamination of meat samples with pathogenic E. coli usually indicates poor hygiene during slaughter and handling, and unsuitable storage after slaughter [ 22 , 23 ]. Another source of contamination is meat supplied from unauthorized abattoirs (e.g., no proper hygiene inspections by authorities), which is then sold at local retail meat shops.…”
Section: Discussionsupporting
confidence: 90%
“…Studies carried out with E. coli isolated from the poultry production chain have demonstrated variable frequencies of resistance to antimicrobials. However, ampicillin, tetracycline, and nalidixic acid have often been reported to have the highest resistance rates (Elumba et al, 2018;Abraham et al, 2019;Varga et al, 2019;Jahantigh et al, 2020;Musa et al, 2020;Pesciaroli et al, 2020;Rabello et al, 2020). In addition, this study Semina: Ciênc.…”
Section: Tablementioning
confidence: 80%
“…In Valencia City, Bukidnon, the Philippines, isolates of E. coli and Salmonella spp. Collected from retail chicken meat at selected markets were resistant to amoxicillin and ampicillin [ 16 ]. Legario et al [ 17 ] reported recovery of Streptococci from Nile tilapia farmed in the Philippines, exhibiting resistance to oxolinic acid and sulphamethoxazole–trimethoprim.…”
Section: Discussionmentioning
confidence: 99%